1996
DOI: 10.1136/jech.50.3.334
|View full text |Cite
|
Sign up to set email alerts
|

The need and demand for renal replacement therapy in ethnic minorities in England.

Abstract: Study objective -The study aimed to determine the relative risk of being accepted for renal replacement treatment of black and Asian populations compared with whites in relation to age, sex, and underlying cause. The implications for population need for renal replacement therapy in these populations and for the development of renal services were also considered. crude relative acceptance rates compared with whites were 3 5 and 3-2 respectively. Age sex specific relative acceptance ratios increased with age in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 22 publications
4
107
1
1
Order By: Relevance
“…However, in the United Kingdom, in those with diabetes, South Asians are known to have a 13-fold increase in risk for ESRD compared with Europeans (30), and in those without diabetes, South Asians have a 3.5-fold increase in risk (28,30,31). A large US primary care study of people with diabetes found that those of Asian origin without hypertension had two-fold prevalence of microalbuminuria (32).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…However, in the United Kingdom, in those with diabetes, South Asians are known to have a 13-fold increase in risk for ESRD compared with Europeans (30), and in those without diabetes, South Asians have a 3.5-fold increase in risk (28,30,31). A large US primary care study of people with diabetes found that those of Asian origin without hypertension had two-fold prevalence of microalbuminuria (32).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…For patients with missing ethnicity data on the UKRR database, ethnicity was updated in a hierarchical order: from the UK Transplant database, the independent organization responsible for maintaining the national organ donor register in the UK, using the name-recognition software program SANGRA, developed and validated in the UK to identify South Asian ethnic origin by name (20); and finally by recoding patients with missing ethnicity as Whites if they lived in a UK Census 2001 ward that had a predominant White population (Ͼ98%). The incidence of RRT is three to four times higher in ethnic minorities compared with Whites in the UK (21,22), and therefore updating ethnicity using Census statistics could potentially lead to a misclassification error of up to 6% to 8%, which was considered acceptable. Patients whose ethnicity could not be updated by the above methods and those with missing primary renal disease and residence postcode were excluded from the study.…”
Section: Study Populationmentioning
confidence: 99%
“…2,4 Data from the Thames region in the early 1990s confirmed that the non-diabetic South Asian population had an age-adjusted relative risk of developing ESRD of 3.5 compared to the white European population, and the African Caribbean population had an increased risk of 3.2. 5 In the African Caribbean population, hypertension and type 2 diabetes are the dominant causes of ESRD, with an additional important influence of sickle cell disease. In South Asians, not only are there significant increases in diabetic nephropathy, but also of most types of glomerulonephritis (confirmed by renal biopsy) as well as reflux nephropathy.…”
Section: Non-diabetic Renal Failurementioning
confidence: 99%